Impacts of APOE-ε4 and exercise training on brain microvascular endothelial cell barrier function and metabolismResearch in context - Callie M. Weber; Bilal Moiz; Gabriel S. Pena; Marzyeh Kheradmand; Brooke Wunderler; Claire Kettula; Gurneet S. Sangha; J. Carson Smith; Alisa Morss Clyne (EBioMedicine)
Summary: Background: The APOE-ε4 genotype is the highest genetic risk factor for Alzheimer's disease (AD), and exercise training can reduce the risk of AD. Two early pathologies of AD are degradation of tight junctions between brain microvascular endothelial cells (BMEC) and brain glucose hypometabolism. Therefore, the objective of this work was to determine how the APOE-ε4 genotype and serum from exercise trained individuals impacts BMEC barrier function and metabolism. Methods: iPSC homozygous for the APOE-ε3 and APOE-ε4 alleles were differentiated to BMEC-like cells and used to measure barrier function and metabolism. To investigate exercise effects, serum was collected from older adults pre- and post- 6 months of exercise training (n = 9 participants per genotype). APOE-ε3 and APOE-ε4 BMEC were treated with genotype-matched serum, and then barrier function and metabolism were measured. Findings: APOE-ε4 genotype impaired BMEC barrier function and metabolism by reducing sirtuin 1 (SIRT1) levels by 27% (p = 0.0188) and baseline insulin signalling by 37% (p = 0.0186) compared to APOE-ε3 BMEC. Exercise-trained serum increased SIRT1 by 33% (p = 0.0043) in APOE-ε3 BMEC but decreased SIRT1 by 22% (p = 0.0004) in APOE ε4 BMEC. Interpretation: APOE-ε4 directly impairs glucose metabolism and barrier function. Serum from exercise trained individuals alters SIRT1 in a genotype-dependent manner but may require additional cues from exercise to decrease AD pathologies. Funding: Brain and Behaviour Initiative at the University of Maryland through the Seed Grant Program, NSF-GRFP DGE 1840340, Fischell Fellowship in Biomedical Engineering, NSF CBET-2211966 and DGE-1632976, National Niemann-Pick Disease Foundation, University of Maryland ASPIRE Program, NIH R01HL165193, R01HL140239-01, and R01AG057552.